Nose-to-Brain delivery of insulin for Alzheimer's disease - Martina Stützle; Johannes Flamm; Stefan Carle; Katharina Schindowski (International Association of Physical Chemists (IAPC), 2015)
The transport of small molecules, peptides and proteins via the olfactory epithelium and along olfactory and trigeminal nerve pathways from the nasal cavity to the brain is very well known and clinically established for central nervous system (CNS) active drugs like oxytocin, sumatriptan or insulin. Insulin is a clinically well-established biopharmaceutical with a validated function in cognition. Central supply with insulin via intranasal administration improves cognition in animal models and in human, making insulin a so-called cognitive enhancer. Furthermore, dysregulation of insulin is implicated in the pathogenesis of Alzheimer's disease, which is associated with lower levels of insulin in the cerebrospinal fluid and is involved in amyloid-beta (Ab) regulation. Clinical trials with intranasal insulin implicate positive effects on learning and memory, but a massive lack of pharmacokinetic and efficacy data hamper a pharmacokinetic - pharmcodynamic relation and a possible clinical development as cognition enhancer. A lack of such data also prevents resolving the mechanisms involved in directing insulin to the central or to the peripheral compartment. Here we discuss the basic mechanism of Nose-to-Brain delivery, evidences for intranasal insulin as cognition enhancer, medical devices for intranasal delivery and safety aspects.